Seamless Access to cancer patient’s EMR through Short Message Service and 2D Barcode - Abd Ghani, M. K.; G. Noma, N (2011)
During doctor-patient consultation, the healthcare professional will require prompt access and accurate patient medical records from past surgeries to blood test, allergies to ultra sound exams and drug prescriptions for delivering accurate and effective healthcare services. The emerging of electronic health record and telecommunication technologies has brought tremendous benefits in healthcare. This paper proposes teleoncology system for seamless access of cancer patient’s health record through short message service. The system used 2D barcode technology and portable storage devices for storing electronic patient health record and encoded the data in the form of quick response code.